An Analysis of Personal Technology Use by Service Members and Military Behavioral Health Providers. Issue 7 (1st July 2016) - Edwards-Stewart, Amanda; Smolenski, Derek J.; Reger, Greg M.; Bush, Nigel; Workman, Don E.
ABSTRACT: Personal technology use is ubiquitous in the United States today and technology, in general, continues to change the face of health care. However, little is known about the personal technology use of military service members and the behavioral health care providers that treat them. This study reports the technology use of 1, 101 active duty service members and 45 behavioral health care providers at a large military installation. Participants reported Internet usage; ownership of smartphones, tablets, and e-readers; usage of mobile applications (apps); and basic demographic information. Compared with providers, service members reported higher rates of smartphone ownership, were more likely to own Android smartphones than iPhones, and spent more time gaming. Both groups spent a comparable amount of time using social media. With the exception of gaming, however, differences between service members and providers were not statistically significant when demographics were matched and controlled. Among service members, younger respondents (18–34) were statistically more likely than older respondents (35–58) to own smartphones, spend time gaming, and engage in social media. Our findings can help inform provider's technology-based education and intervention of their patients and guide the development of new technologies to support the psychological health of service members.